Association between body size and selected hematological parameters in men and women aged 45 and above from a hospitalized population of older adults: an insight from the Polish Longitudinal Study of Aging (1960–2000) - Chmielewski, Piotr; Strzelec, Bartłomiej; Chmielowiec, Jolanta; Chmielowiec, Krzysztof; Borysławski, Krzysztof (Anthropological Review, 2017)
In elderly people, anemia occurs with increasing frequency with each advancing decade and can be a harbinger of very serious health conditions, including gastrointestinal bleeding, gastric and duodenal ulcers, and cancer. Therefore, age-dependant changes in hematological parameters deserve special attention. Nonetheless, very few longitudinal studies of aging have focused on possible associations between basic anthropometric characteristics and hematological parameters in older people. Here, we present some evidence that body size can be associated with red blood cell count as well as some other selected hematological parameters in adults aged 45 to 70 years. Longitudinal data on anthropometric and hematological parameters have been obtained from physically healthy residents at the Regional Psychiatric Hospital for People with Mental Disorders in Cibórz, Lubuskie Province, Poland (142 individuals, including 68 men and 74 women). The residents who took psychoactive drugs were excluded from the study. To evaluate the studied relationships, three anthropometric traits were used and three dichotomous divisions of the study sample were made. The medians of body height, body weight, and body mass index at the age of 45 years were used to divide the sample into: shorter and taller, lighter and heavier, and slimmer and stouter individuals, respectively. Student’s t-test, Pearson’s correlation, and regression analysis were employed. The results of the present study suggest that the relationship between body size and red blood cell count is slightly more pronounced in men and its strength depends on age. However, the correlations between body size and red blood cell count proved to be weak in both sexes. With aging, the strength of the relation decreased gradually, which might have been caused by the aging-associated changes in the hematopoietic system, anemia, or was an artifact. Further studies are needed to elucidate the unclear association between body size and hematological parameters in older adults.